Incivilidade à mesa?: comer com desconhecidos - Araújo, Daniel Séjour (2012)
This research has as its object the relations established among individuals who do not know each other at restaurants in the central area of Uberlândia - MG. It was carried out from the perspective of the study of everyday life as a way to perceive the experiences of the common man in the processes of societal change. We conducted a case study through observations and interviews in which we seek to apprehend the representations of the patrons of establishments that have a particular feature, almost mandatory, that their clients share a table. From the theoretical references which allow considering food as a means for the analysis of social relations; the construction of rules of behavior in society; eating out and the changes of the interactions in public space, we analyze how the definitions of behaviors considered appropriate for the occasion affect relations among strangers in the restaurant area. We could see that the behavior shared by clients have the effect of dismissing the strangers, through rules that guide people\'s attitudes so as not to disrespect others.